Characterization of recombinant yellow fever-dengue vaccine viruses with human monoclonal antibodies targeting key conformational epitopes. Issue 32 (26th July 2019) - Lecouturier, Valerie; Berry, Catherine; Saulnier, Aure; Naville, Sophie; Manin, Catherine; Girerd-Chambaz, Yves; Crowe, James E.; Jackson, Nicholas; Guy, Bruno
Highlights: The CYD-TDV vaccine displays epitopes targeted by potent serotype-specific and cross-reactive neutralizing human antibodies. The CYD-2 envelopes display epitopes specific of the mature conformation. The CYD-TDV has the ability to trigger antibody responses qualitatively similar to those induced by wild-type viruses. Abstract: The recombinant yellow fever-17D–dengue virus, live, attenuated, tetravalent dengue vaccine (CYD-TDV) is licensed in several dengue-endemic countries. Although the vaccine provides protection against dengue, the level of protection differs by serotype and warrants further investigation. We characterized the antigenic properties of each vaccine virus serotype using highly neutralizing human monoclonal antibodies (hmAbs) that bind quaternary structure-dependent epitopes. Specifically, we monitored the binding of dengue virus-1 (DENV-1; 1F4), DENV-2 (2D22) or DENV-3 (5J7) serotype-specific or DENV-1–4 cross-reactive (1C19) hmAbs to the four chimeric yellow fever-dengue vaccine viruses (CYD-1–4) included in phase III vaccine formulations using a range of biochemical and functional assays (dot blot, ELISA, surface plasmon resonance and plaque reduction neutralization assays). In addition, we used the "classic" live, attenuated DENV-2 vaccine serotype, immature CYD-2 viruses and DENV-2 virus-like particles as control antigens for anti-serotype-2 reactivity. The CYD vaccine serotypes were recognized by each hmAbs with the expected specificity, moreover, surface plasmon resonance indicated a high functional affinity interaction with the CYD serotypes. In addition, the hmAbs provided similar protection against CYD and wild-type dengue viruses in the in vitro neutralization assay. Overall, these findings demonstrate that the four CYD viruses used in clinical trials display key conformational and functional epitopes targeted by serotype-specific and/or cross-reactive neutralizing human antibodies. More specifically, we showed that CYD-2 displays serotype- specific epitopes present only on the mature virus. This indicates that the CYD-TDV has the ability to elicit antibody specificities which are similar to those induced by the wild type DENV. Future investigations will be needed to address the nature of CYD-TDV-induced responses after vaccine administration, and how these laboratory markers relate to vaccine efficacy and safety.